STATISTICAL ANALYSIS OF THE GENERALIZED INTEGRAL INDICATOR OF THE SOCIO-ECONOMIC SITUATION OF THE SUBJECTS OF THE RUSSIAN FEDERATION - L. Davletshina; T. Pershina (Вестник университета)
In the conditions of socio-economic development of the country the issue of analysis of the subjects of the Russian Federation is especially acute. This analysis covers the widest range of social and economic indicators of the country’s regions, which allows identifying the most lagging social or economic blocks in order to build a further development plan for the region. The integral indicator of the social and economic situation of the subjects of the Russian Federation is proposed as the main characteristic. To build a generalized indicator, the data of the Federal State Statistics Service were used. Ranking of regions by federal districts, as well as clustering of the country’s subjects according to the selected indicators, allows more accurately determining developing and lagging regions.